Distal protein-protein interactions contribute to nirmatrelvir resistance - Eric M. Lewandowski; Xiujun Zhang; Haozhou Tan; Aiden Jaskolka-Brown; Navita Kohaal; Aliaksandra Frazier; Jesper J. Madsen; Lian M. C. Jacobs; Jun Wang; Yu Chen (Nature Communications)
Abstract SARS-CoV-2 main protease, Mpro, is responsible for processing the viral polyproteins into individual proteins, including the protease itself. Mpro is a key target of anti-COVID-19 therapeutics such as nirmatrelvir (the active component of Paxlovid). Resistance mutants identified clinically and in viral passage assays contain a combination of active site mutations (e.g., E166V, E166A, L167F), which reduce inhibitor binding and enzymatic activity, and non-active site mutations (e.g., P252L, T21I, L50F), which restore the fitness of viral replication. To probe the role of the non-active site mutations in fitness rescue, here we use an Mpro triple mutant (L50F/E166A/L167F) that confers nirmatrelvir drug resistance with a viral fitness level similar to the wild-type. By comparing peptide and full-length Mpro protein as substrates, we demonstrate that the binding of Mpro substrate involves more than residues in the active site. Particularly, L50F and other non-active site mutations can enhance the Mpro dimer-dimer interactions and help place the nsp5-6 substrate at the enzyme catalytic center. The structural and enzymatic activity data of Mpro L50F, L50F/E166A/L167F, and others underscore the importance of considering the whole substrate protein in studying Mpro and substrate interactions, and offers important insights into Mpro function, resistance development, and inhibitor design.